Aerobic Batch Degradation of Cresol by Newly Isolated Pseudomonas monteilii Cr13 - N.K. Shainy; R. Usha (Journal of Pure and Applied Microbiology, 2018)
Microorganisms have broad spectrum of applications varying from metabolite production to breakdown of complex carbon sources. Cresols are one such complex that has drawn attention due to its disposal in un-degraded or partially degraded form that enters into air, water and soil polluting the environment; its extremities extend to surrounding ecosystem and destroying the aquatic and human life forms. Cresol possesses special affection towards blood plasma leading to kidney, liver and heart disorders. Many have reported biological degradation of hazardous chemical using different organisms with fine degradation efficiency. The current investigation adds another strain Pseudomonas monteilii which was found to exhibit the potential to utilize cresol as its major carbon source for growth and proliferation. Further, the Cresol inhibitory concentration was checked by varying concentration from 100 to 1500 ppm. The remnant concentration over the time period was analyzed by aminoantipyrine assay. The strain was capable of >99% removal at neutral pH, 150 rpm and 30p C in 24h. The phylogeny of the strain was analyzed post 16S rRNA sequencing using in silico tools. The strain can be optimized for degrading higher cresol dose without compromising on the biodegradation efficiency.